Construction and Implementation of an Expert System for Medical Diagnosis Based on Blood Test - Ibraheem Nadher Ibraheem (Tikrit Journal of Pure Science)
The recent developments in the field of artificial intelligence to the emergence of expert systems, and computational tools designed to capture and access to knowledge from experts in the medical field. We have built an expert system for the purpose of giving the diagnosis of some diseases by linking this system devise testing and analysis of blood type (CELL-DYN Ruby) and which has a private entrance to the computer. The system is divided into several modules, History Entering Module (HEM) systematic Review Module (SRM), a Laboratory Test List Module, Diagnosis Process Module (DPM), Data Base (DB), and finally the graphical interface to the user.